2013
DOI: 10.1111/bph.12440
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide exerts anti‐hepatitis C virus activity by up‐regulating haeme oxygenase‐1 via the p38 MAPK/Nrf2 pathway in human hepatoma cells

Abstract: BACKGROUND AND PURPOSEThis study aimed to evaluate the anti-hepatitis C virus (HCV) activity of andrographolide, a diterpenoid lactone extracted from Andrographis paniculata, and to identify the signalling pathway involved in its antiviral action. EXPERIMENTAL APPROACHUsing HCV replicon and HCVcc infectious systems, we identified anti-HCV activity of andrographolide by measuring protein and RNA levels. A reporter activity assay was used to determine transcriptional regulation of anti-HCV agents. A specific inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
97
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(107 citation statements)
references
References 57 publications
3
97
0
Order By: Relevance
“…AGP, the major active ingredient of the herbal medicine A. paniculata, has been shown to exert various biological activities, including antitumor (Yang et al, 2014), anti-inflammatory (Ku and Lin, 2013), antiviral (Wen et al, 2014), and hepatoprotective effects (Lee et al, 2014). In this study, we showed that AGP significantly inhibited RANKL-induced osteoclast differentiation from RAW 264.7 murine macrophage cells and decreased the number of osteoclasts and the mRNA expression of TRAP.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…AGP, the major active ingredient of the herbal medicine A. paniculata, has been shown to exert various biological activities, including antitumor (Yang et al, 2014), anti-inflammatory (Ku and Lin, 2013), antiviral (Wen et al, 2014), and hepatoprotective effects (Lee et al, 2014). In this study, we showed that AGP significantly inhibited RANKL-induced osteoclast differentiation from RAW 264.7 murine macrophage cells and decreased the number of osteoclasts and the mRNA expression of TRAP.…”
Section: Discussionmentioning
confidence: 51%
“…Several studies have demonstrated that AGP exhibits various biological activities, including antitumor (Yang et al, 2014), anti-inflammatory (Ku and Lin, 2013), antiviral (Wen et al, 2014), and hepatoprotective effects (Lee et al, 2014). It has been demonstrated that AGP can attenuate inflammation by inhibiting NF-kappaB activation through covalent modification of the reduced cys62 residue of p50 (Xia et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A. paniculata has long been used as herbal medicine for the prevention and treatment of upper respiratory tract infection in Asian countries and in Scandinavia (14). Andrographolide has been shown to possess various biological activities, including antiviral (15), anticancer (13,16), anti-inflammatory (17,18) and antioxidative (15,19,20) activities.…”
mentioning
confidence: 99%
“…Indeed, this pathway regulates the expression of key antioxidant enzymes that are involved in the neutralization of oxidants generated during viral infections. In addition, the Nrf2 pathway has also been demonstrated to exert antiviral effect against viruses such as hepatitis C virus, respiratory syncytial virus (RSV), and influenza viruses (31)(32)(33)(34)(35). Interestingly, some studies showed that Nrf2 activators, such as sulforaphane and epigallocatechin gallate, significantly decrease influenza virus entry and replication in nasal and alveolar epithelial cells (32,36).…”
Section: Discussionmentioning
confidence: 99%